Network Modeling of Rational Value Systems Interaction: Justification of the Basic Principles and Methodology - Kondratenko, Konstantin S. (Journal on Interactive Systems, 2026)
Background: the article is devoted to the study of the interaction of rational-value systems, thus being an integral part of the theory of rational systems. Purpose: the purpose of the article is to develop a methodology for network modeling of rational-value systems (RVS) based on the analysis of their interaction, proposing a classification of networks (egocentric, communicative, convergent and cause-and-effect) and substantiating their application. Methods: the main method of this work is network analysis used in social sciences. Results: the article substantiates the possibility of network modeling of rational-value communication. Both general principles and examples of a network model and a data window, as well as special cases in the form of network types are presented. The most promising include the egocentric and cause-and-effect network model. Conclusion: in the conclusion, conclusions and generalizations are made, further directions for the study of rational systems are formulated. This article briefly describes the basic principles of rational-value communication, provides an example of network modeling and windows of calculation data provided in a previously published article, but not included in it. In addition, this article expands the author’s ideas in the direction of network modeling options.